The impact of lactic acid bacteria inoculation on the fermentation and metabolomic dynamics of indigenous Beijing douzhi microbial communities - Han, Dong; Bao, Xinyu; Wang, Yanfang; Liao, Xiaohong; Wang, Ke; Chen, Jian; Li, Xiaolong; Yang, Zhennai; Wang, Yanbo (Frontiers in Microbiology, 2024)
Background: Douzhi, a traditional Chinese fermented beverage, features microbial communities primarily composed of lactic acid bacteria (LAB). As fermented foods continue to gain recognition and popularity, douzhi is attracting growing interest.However, investigation of the critical aspects of douzhi's fermentation processes, including fermentation characteristics and microbial community dynamics, remains vital for enhancing food safety and quality for douzhi, as well as for similar fermented food products.In this study, we collected douzhi microbial communities from four chain stores, using them as fermentation starter cultures. The microbial dynamics of the fermentation were analyzed, focusing on the inoculation of LAB strains and the transition from a mung bean-based matrix to skimmed milk. The metabolomic profiles of the fermented mung bean matrices were also studied.Results: Douzhi samples obtained from representative chain stores were found to be overwhelmingly dominated by LAB. When inoculated along with the douzhi community, both LAB strains exhibited notable and substantial reductions in the pH value of the designated mung bean matrices compared to those inoculated indigenous microbiota. Specifically, Lactiplantibacillus plantarum CGMCC 1.1856 retained its population, whereas Pediococcus pentosaceus CGMCC 1.2695 exhibited a decrease in relative abundance. Using skimmed milk as a fermentation substrate instead of the mung bean matrix resulted in significant shifts in microbial communities, particularly leading to an increase in Escherichia sp. The metagenomic analyses and functional predictions illustrated that various metabolic functions were enhanced during the fermentation process due to LAB inoculation. The liquid chromatography-mass spectrometry based metabolomic analysis revealed that the inoculation of Lactiplantibacillus plantarum and Pediococcus pentosaceus in mung bean matrix did not introduce new metabolites but significantly altered the concentration and profile of existing metabolites, especially increased low molecular carbohydrates, which may enhance the nutritional potential of the fermented product.Discussion: This study examines the microbial dynamics of douzhi microbiota fermentation, emphasizing the role of lactic acid bacteria in enhancing fermentation activity and metabolite profiles. These insights contribute to improving manufacturing processes and ensuring the safety and quality of douzhi and similar fermented foods.